Eng - Sabri, Muhammad Faiz; Saleh, Suhaila Mohd; Rahmat, Mohd Khairezan (ITB Journal Publisher, DRPM ITB, 2025)
Craft products are among the most intricate and unique artifacts produced by indigenous people in the Malay Peninsula. They have also become a major attraction for tourists to come and visit Malaysia. For hundreds of years, the indigenous people known as Orang Asli have extensively produced different art forms that reflect their philosophy and belief system. This study aimed to investigate in-depth the artistic expressions of craft motifs and ornaments produced by Orang Asli, specifically in Kuala Lipis Pahang, Malaysia. The objectives of this study were to determine the types of motifs in Orang Asli craftwork; to investigate the different elements of motifs that appear in Orang Asli craftwork; and to analyze the meaning embedded in selected motifs of Orang Asli craftwork. This study employed a case study approach through a series of interviews with experts, or traditional craftsmen, followed by observations as well as document analysis. This study highlights the beauty of traditional Orang Asli craftsmanship, which needs to be revisited and showcased in order to preserve their important culture and heritage for future generations.